Isoliquiritigenin Protects Against Pancreatic Injury and Intestinal Dysfunction After Severe Acute Pancreatitis via Nrf2 Signaling - Zhang, Man; Wu, Yan-Qing; Xie, Ling; Wu, Jiang; Xu, Ke; Xiao, Jian; Chen, Da-Qing (Frontiers in Pharmacology, 2018)
Severe acute pancreatitis (SAP) is a digestive system disease that is associated with a range of complications including intestinal dysfunction. As current treatment strategies are inadequate, SAP causes considerable morbidity and mortality. In this study, we determined that the chalcone compound, isoliquiritigenin (ISL), reduces pancreatic and intestinal injury in a mouse model of SAP. These effects were achieved by suppressing oxidative stress and the inflammatory responses to SAP. This was evidenced by a reduction in histological score, and malondialdehyde(MDA), serum interleukin (IL)-6, tumor necrosis factor (TNF)-α and cleaved-caspase-3(c-caspase-3) protein along with an increase in Nrf2, hemeoxygenase-1 (HO-1), quinone oxidoreductase 1 (NQO1) and superoxide dismutase (SOD). We then used Nrf2-/- mice to test the protective effect of Nrf2 during ISL treatment of SAP. Our results indicated that Nrf2-/- mice had greater pancreatic injury and intestinal dysfunction than wild-type mice. After SAP, the Nrf2-/- mice had greater histological scores, MDA, C-caspase-3 activity, and TNF-α and IL-6 release along with lower SOD, HO-1and NQO-1 compared with the wild-type mice. They also had reduced adherens junctions(P120-catenin) and tight junctions (occludin),and increased activated nuclear factor-κB (NF-κB) protein. In the Nrf2-/- mice, ISL was less effective at inhibiting the activity of NF-κB and repairing intestinal barrier function than in the WT mice. In conclusion, this study demonstrates that ISL exerts its protective effects against oxidative stress and inflammatory injury after SAP via regulation of the Nrf2/NF-κB pathway. It also showed that the efficacy of ISL in repairing the intestinal barrier damage caused by SAP is closely related to the Nrf2 protein. Our findings demonstrate that Nrf2 is an important protective factor against SAP-induced oxidative stress, inflammatory response, apoptosis and destruction of the intestinal barrier.